2019
DOI: 10.5217/ir.2018.00114
|View full text |Cite
|
Sign up to set email alerts
|

Does fecal calprotectin equally and accurately measure disease activity in small bowel and large bowel Crohn’s disease?: a systematic review

Abstract: Fecal calprotectin (FC) is a highly sensitive disease activity biomarker in inflammatory bowel disease. However, there are conflicting reports on whether the diagnostic accuracy in Crohn’s disease is influenced by disease location. The aim of this study was to undertake a systematic review of the published literature. Relevant databases were searched from inception to November 8, 2016 for cohort and case control studies which had data on FC in patients with isolated small bowel (SB) and large bowel (LB) Crohn’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 75 publications
3
45
0
1
Order By: Relevance
“…FC is a useful surrogate marker to detect bowel inflammation and to diagnose and monitor patients with inflammatory bowel diseases. 22,[41][42][43][44][45] Mosli et al 42 reported that endoscopic activity in symptomatic patients with inflammatory bowel diseases could be detected by FC with a pooled sensitivity of 0.88 (95% CI, 0.84 to 0.90) and specificity of 0.73 (95% CI, 0.66 to 0.79). Another recent meta-analysis showed that an FC cutoff of 150 μg/g could be used to detect a postoperative endoscopic recurrence of Crohn's disease (pooled sensitivity was 0.70 [95% CI, 0.59 to 0.81], specificity, 0.69 [95% CI, 0.61 to 0.77], and DOR, 5.92 [95% CI, 2.61 to 12.17]).…”
Section: Discussionmentioning
confidence: 99%
“…FC is a useful surrogate marker to detect bowel inflammation and to diagnose and monitor patients with inflammatory bowel diseases. 22,[41][42][43][44][45] Mosli et al 42 reported that endoscopic activity in symptomatic patients with inflammatory bowel diseases could be detected by FC with a pooled sensitivity of 0.88 (95% CI, 0.84 to 0.90) and specificity of 0.73 (95% CI, 0.66 to 0.79). Another recent meta-analysis showed that an FC cutoff of 150 μg/g could be used to detect a postoperative endoscopic recurrence of Crohn's disease (pooled sensitivity was 0.70 [95% CI, 0.59 to 0.81], specificity, 0.69 [95% CI, 0.61 to 0.77], and DOR, 5.92 [95% CI, 2.61 to 12.17]).…”
Section: Discussionmentioning
confidence: 99%
“…A sensitivity analysis which excluded patients with “borderline” faecal calprotectin values was performed to address this and confirmed all findings from the primary analysis. There is additional concern the accuracy of faecal calprotectin may be lower in ileal disease, 9 but in this cohort only one patient had isolated ileal disease and they had a very raised calprotectin level over 2000 μg/g.…”
Section: Discussionmentioning
confidence: 88%
“…Low faecal calprotectin levels are a well validated non‐invasive marker of mucosal healing in CD 3‐6 . The faecal calprotectin threshold which defines mucosal healing has not been universally agreed, studies support values in the range of 100‐300 μg/g, 3‐8 with a value of 100 μg/g used most frequently 9 . In paediatric CD Weinstein‐Nakar et al 7 found faecal calprotectin levels under 100 μg/g were predictive of mucosal and transmural healing.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity and specificity of fecal calprotectin testing are dependent on the location of the inflammation. Several studies reported lower specificity in CD patients versus UC patients, and higher specificity for large bowel disease versus small bowel disease 24 . Approximately 80% of CD patients have ileal involvement and up to 32% have isolated small bowel disease.…”
Section: Discussionmentioning
confidence: 99%